Teaching plagiarism prevention to college students an ethics-based approach - Strittmatter, Connie; Bratton, Virginia K. (Rowman & Littlefield, 2016)
This publication provides an innovative approach to plagiarism instruction grounded in ethics theory. It provides tools to address why plagiarism is an important ethical issue in an academic environment. This book introduces general principles of ethics adaptable to plagiarism prevention instruction in a variety of learning settings.